Dampak E-Servive Quality Terhadap E-Satisfaction Serta Implikasinya Pada Online Repurchase B2C Shopee.com - Raras Ivastya; Zaenal Fanani (Esensi: Jurnal Bisnis dan Manajemen, 2020)
Internet services that were introduced in 1993 have an impact on behavior change and the ways of consumer decisions making. On the other hand, the emergence of various developments in information technology, connectivity and smartphones are also slowly able to change the way of consumers for meet the needs of a product or service. This research was conducted for intention to examine the effect of e-service quality on e-satisfaction and implications on B2C consumer repurchase online. Data was taken using an online questionnaire and distributed to B2C consumers with the last amount of data collected as many as 312 questionnaires and then be analyzed using the partial least square method. The results of the analysis show that e-service quality provides a significant positive effect on e-satisfaction and online repurchase for B2C consumers. In other results show e-satisfaction has a significant effect on online repurchase and is able to be a partial mediator of the relationship of e-service quality with online repurchase of B2C consumers.